2018
DOI: 10.1186/s12884-018-2006-8
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of cardiac time intervals utilising non-invasive fetal electrocardiogram in normal fetuses

Abstract: BackgroundNon-invasive fetal electrocardiogram (NIFECG) is an evolving technology in fetal surveillance which is attracting increasing research interest. There is however, only limited data outlining the reference ranges for normal cardiac time intervals (CTIs). The objective of our group was to carry out a systematic review to outline normal fetal CTIs using NIFECG.MethodsA systematic review of peer reviewed literature was performed, searching PUBMED,Ovid MEDLINE and EMBASE. The outcomes of interest included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…Broadly speaking, these encompass signal detection, enhancement, waveform detection and techniques for signal enhancement. These techniques however are beyond the scope of the review but can be accessed from previous work by our group [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Broadly speaking, these encompass signal detection, enhancement, waveform detection and techniques for signal enhancement. These techniques however are beyond the scope of the review but can be accessed from previous work by our group [31].…”
Section: Discussionmentioning
confidence: 99%
“…The temporal intervals of significance include the P wave duration, PR interval, QRS duration, QT interval and T/QRS ratio. Information regarding these parameters can be sourced from previous work by our group [31] .
Fig. 3Cardiac time intervals illustrated on a fetal ECG beat.
…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a bio-electromagnetism perspective, the simple volume conductor approximation assumed the maternal body organs, layers of tissue and fat and amniotic fluid only attenuating the propagation of the fECG signal towards the maternal abdominal electrodes, which holds for early pregnancy but not throughout the whole gestation 36 , 37 . The layer with the lowest conductivity is the vernix caseosa , a protective waxy substance that covers the foetus that can greatly attenuate or even suppress the fECG 38 . Pioneering studies revealed how this substance presents an electrical impedance that is two orders of magnitude higher than that of amniotic fluid and foetal/maternal tissue 39 .…”
Section: Methodsmentioning
confidence: 99%